Which of the following is a equivalent form of the equation
![Which of the following is a equivalent form of the equation class=](https://us-static.z-dn.net/files/db6/60cb8c6dfd2f460aac86d96df82d24d1.jpg)
Answer:
[tex]c.\ \ \ \ y=(x-a)(x+b)[/tex]
Step-by-step explanation:
-The equation [tex]y=x^2-ax+bx-ab[/tex] can be simplified by grouping like terms together:
[tex]y=x^2-ax+bx-ab\\\\\#Group \ terms \ with \ x \ and \ a\\\\\\=x^2+bx-ax-ab[/tex]
#we then introduce brackets:
[tex]x^2+bx-ax-ab\\\\x(x+b)-a(x+b)\\\\\\(x-a)(x+b)[/tex]
we equate to y:
[tex]y=(x-a)(x+b)[/tex]
Hence, the equitation's equivalent form is [tex]y=(x-a)(x+b)[/tex]